Combining the genetic algorithm and successive projection algorithm for the selection of feature wavelengths to evaluate exudative characteristics in frozen–thawed fish muscle - Cheng, Jun-Hu; Sun, Da-Wen; Pu, Hongbin (Food chemistry, 2016)
•Hyperspectral imaging was used to predict drip loss in frozen–thawed fish.•Five key wavelengths were selected by combination of GA and SPA.•GA–SPA–LS-SVM and GA–SPA–MLR models showed satisfactory performances.•The distribution maps of drip loss were generated. The potential use of feature wavelengths for predicting drip loss in grass carp fish, as affected by being frozen at −20°C for 24h and thawed at 4°C for 1, 2, 4, and 6days, was investigated. Hyperspectral images of frozen–thawed fish were obtained and their corresponding spectra were extracted. Least-squares support vector machine and multiple linear regression (MLR) models were established using five key wavelengths, selected by combining a genetic algorithm and successive projections algorithm, and this showed satisfactory performance in drip loss prediction. The MLR model with a determination coefficient of prediction (R2P) of 0.9258, and lower root mean square error estimated by a prediction (RMSEP) of 1.12%, was applied to transfer each pixel of the image and generate the distribution maps of exudation changes. The results confirmed that it is feasible to identify the feature wavelengths using variable selection methods and chemometric analysis for developing on-line multispectral imaging.